Discourse Marker in Research Seminar - Pujalinda Mandarsari; Fredy Akbar K (Journal of Applied Linguistics, 2023)
Discourse markers is a word or a phrase that useful in communication. This paper investigates the use of discourse markers in research seminar. The objectives of this study are to find out the types and the functions of Discourse Markers used by the participants in the research seminar. The researcher analyzed the use of discourse markers based on Brinton Theory that are Brinton’s Inventory and Brinton’s Function Inventory. The results of the study contain two finding. First, there are eleven types of DMs that found based on Brinton’s Inventory, they are well, okay, and, if, but, because, I mean, oh, right, so and yes (DM yes is in Indonesian form like iya and in south Sulawesi form that is iye.). While, DMs that does not contain in Brinton’s Inventory, that is DM ya. Second, the function of discourse markers used by participants in research seminar have several functions that is based on the context. Based on Brinton’s Function Inventory, there are two function of discourse markers are textual function and interpersonal function. Keywords: Brinton theory, discourse markers, research seminar